Categorizing world regional art prices by artistic movement: an analysis of Latin American art - Garay, Urbi (2025)
Purpose: The literature on the potential benefits of art investing has yet to consider the effects of categorizing world regional art markets (e.g. Latin American art) by artistic styles or movements (e.g. Latin American surrealism, Latin American conceptual art, etc.). We propose that such categorization should be carried out and analyze the Latin American art market as an example. Design/methodology/approach: Eleven artistic style price indices within the Latin American art market (30,288 artworks created by 293 artists and sold at auction between 1970 and 2014) are estimated using hedonic regressions: Abstract-geometric, abstract-informal, conceptual, costumbrismo, cubism, figurative, muralism, landscape, surrealism, nineteenth century and avant-garde. We find that several variables that rely on the corresponding Latin American art movement index have a significant relationship with painting prices. Findings: There is significant variation in the financial performance of the various price indices for Latin American art styles: the conceptual (10.33% annual real return), abstract geometric (1.97%), cubism (0.97%) and costumbrismo (0.91%) movements overperformed a market that exhibited an aggregate negative cumulated real return of 0.9% during the sample period. The average correlation between each of the styles was only 0.12. The estimated price index for paintings sold at Christie's and Sotheby's clearly outperformed the index estimated for the other auction houses, and we also found that paintings created by Latin American women artists yielded higher returns. Practical implications: Our results have practical applications for investors, collectors, auction houses and policymakers. Originality/value: This is the first paper to highlight the need to decompose art price indices by artistic movements at the regional level.